2004
DOI: 10.1592/phco.24.17.1659.52342
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of Commonly Used Equations to Predict Energy Expenditure in Mechanically Ventilated, Critically Ill Patients

Abstract: The Harris-Benedict equation multiplied by an activity factor of 1.2 is suitable for predicting REE and may be used in the absence of indirect calorimetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 19 publications
0
21
0
4
Order By: Relevance
“…The choice for calculating resting energy expenditure (REE) as Harris-Benedict times 1.2 originates from the recommendation by Alexander and colleagues [9] where actual REE are compared with formulas used in the ICU. Also the AARC guidelines uses the Harris-Benedict equation.…”
Section: Methodsmentioning
confidence: 99%
“…The choice for calculating resting energy expenditure (REE) as Harris-Benedict times 1.2 originates from the recommendation by Alexander and colleagues [9] where actual REE are compared with formulas used in the ICU. Also the AARC guidelines uses the Harris-Benedict equation.…”
Section: Methodsmentioning
confidence: 99%
“…For nonobese patients, the Harris-Benedict equation, multiplied by a stress factor of 1.3–1.5 reasonably estimates energy expenditure and therefore, caloric needs in critically ill patients. 19 Nevertheless, this and other estimates may be inaccurate and individual patients may benefit from indirect calorimetry as discussed subsequently. Assessing the patient’s preinjury nutritional and general health status is often difficult and frequently impossible, at least initially.…”
Section: Caloric Requirements and Nutrient Formulationmentioning
confidence: 99%
“…(20,30) However, the results of other authors indicate that the HB equation in an acceptable substitute for IC. (31,32) The latest ESPEN guidelines (8) recommend that, in the absence of IC, the critically ill patient should receive 25 kcal/kg per day and that this value should reached over 2 to 3 days after the beginning of NS. By verifying the average energy requirements of 24.48 kcal/kg/day, our results indicated that overall, the value that is recommended by the European society is suitable for the overall requirement of patients in this ICU, although a slight hyperalimentation may occur, particularly in obese individuals.…”
Section: Discussionmentioning
confidence: 99%